Sosialisasi Sistem Digital Pendaftaran Ujian Sarjana Bebasis Database di Program Studi Pendidikan Fisika - Carolina Sri Athena Barus (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
The development of digital technology in the field of education continues to advance, including in academic administration. This article discusses the socialization of a digital system for undergraduate exam registration based on a database in the Physics Education Study Program. The purpose of this socialization is to introduce and implement a system that simplifies the process for students to register for undergraduate exams online. This system is designed to replace the manual registration method, which is time-consuming and prone to errors. Through this socialization, it is expected that students and academic staff can understand the benefits and how to use this new system. The results of the socialization show that the majority of users are satisfied with the ease and speed offered by this system. This system not only improves operational efficiency but also supports transparency and accuracy in academic data. In conclusion, the implementation of this digital system is a positive step towards modernizing academic services in the Physics Education Study Program.